Communication and stress in organization : a study of relationship among staff members in a Malaysian University. - Hassan, Salleh; Yaacob, Hashim Fauzy (1995)
Stress can occur at home,workplace and in community relation. There are many factors which contribute to stress especially in coping up with work load and social demands of modern life. This study was carried out to find out the level of stress at work among staff members at a Malaysian University and its relationship to communication related factors in an academic organisation. Stress in this study was measured in terms of psychological,physiological and behavioral symptoms. The instrument used was adapted from Dorin (1985). The communication factors included in this study were role in organisation (role conflict and role ambiguity),communication climate (supportiveness,participation in decision making,openness and level of trust);communication structure (relationship with superior,relationship with subordinate and relationship with peers);communication level (information overload and information underload);and communication apprehension (fear to communicate). Selected demographic variables were also included to determine their relationship with stress. This study was conducted at University of Technology Malaysia (UTM) with a total sample of 230 respondents. Sixty percent of the respondent were supporting staff members and the 40 percent were professionals (administrators and academicians). Seven hypotheses were tested using t-test and Pearson Correlation. The t-test was used to reveal the varying level of stress among the staff while the correlation test was used to determine relationships between variables. The results show that the level of stress among UTM staff is moderate. This applies to both professional and support staff. Communication level is also moderate,except for horizontal communication which is high. Stress is found to have significantly positive relationship with all the main communication variables,these are role conflict,role ambiguity,communication climate,communication structure,communication load and communication apprehension. However,amoong the twelve communication variables role conflict,role ambiguity,openness,supportive communication and horizontal communication have a strong relationship compared to other variables. Communication and stress relationship among professional and supporting stafff do not reveal a distinction in correlation,except for participation in decision making.